Mascotas - Watts, Claire; Voce, Louise (Princeton, NJ : Two-Can, 2002)
In simple text and illustrations, describes a variety of pets including cats, fish, rabbits, and dogs.
Includes index.
Accelerated Reader
Keywords: Pets -- Juvenile literature; Mascotas -- Literatura juvenil